PENGGUNAAN MEDIA PHET SIMULATION MATERI LISTRIK DINAMIS TERHADAP MOTIVASI BELAJAR IPA SISWA KELAS IX SMP NEGERI SATAP OEUSAPI-AMANUBAN BARAT - Jannes Bastian Selly; Dirmayati Eklesia Tafuli (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
Abstract. PhET simulation is a platform that can be used as a learning medium to make learning more interesting. The material presented in PhET simulation is in the form of an interesting animation so that it is expected to be able to increase student motivation. This study aims to determine differences in students' motivation to learn physics before and after being taught using PhET simulation media. The research object was class IXB students who were randomly selected as the experimental group. The instruments used were class IX learning devices, PhET simulation media, discussion questions, assignment questions, and student learning motivation questionnaires. Based on statistical analysis, it is known that students' motivation to learn science after being taught using PhET simulation media is higher than before. Thus learning science on dynamic electricity material using PhET simulation media is effective for increasing the learning motivation of class IX students of Satap Oeusapi Public Middle School, West Amanuban District, South Central Timor Regency. Abstrak. Simulasi PhET merupakan salah satu platform yang dapat dimanfaatkan sebagai media pembelajaran untuk membuat pembelajaran lebih menarik. Materi yang disajikan pada phet simulation dalam bentuk animasi yang menarik sehingga diharapkan mampu meningkatkan motivasi belajar siswa. Penelitian ini bertujuan untuk mengetahui perbedaan motivasi belajar fisika siswa sebelum dan setelah diajar menggunakan media simulasi PhET. Obyek penelitian merupakan siswa kelas IXB yang terpilih secara acak sebagai kelompok eksperimen. Instrumen yang digunakan adalah perangkat pembelajaran kelas IX, media simulasi PhET, soal diskusi, soal tugas, serta angket motivasi belajar siswa. Berdasarkan analisis statistik diketahui bahwa motivasi belajar IPA siswa setelah diajar menggunakan media simulasi PhET lebih tinggi dibanding sebelumnya. Dengan demikian pembelajaran IPA pada materi listrik dinamis menggunakan media simulasi PhET efektif untuk meningkatkan motivasi belajar siswa kelas IX SMP Negeri Satap Oeusapi Kecamatan Amanuban Barat, Kabupaten Timor Tengah Selatan.